2010
DOI: 10.1007/s10592-010-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resilience of Daphnia populations following experimental removal of introduced fish

Abstract: Dramatic changes in environmental conditions or community composition may impose severe selective pressures on resident populations. These changes in the selective regime can lead to demographic bottlenecks or local extinction. The consequence of demographic contraction is often a reduction of standing genetic variation. Since the level of adaptive genetic variation in populations plays an important role in persistence and adaptive response, understanding genetic resilience and the time course for re-establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…The presence of diapausing eggs in different sections of the two sediment cores confirmed that their production is a fundamental survival strategy in high-altitude lakes. The accumulation in sediments of diapausing eggs of different species, generations and genotypes, represents a potential reserve of biodiversity [12,16], which buffers the consequent extinction risk from anthropogenic impacts and makes the population resilient to the settlement of invasive species [50,51]. Organisms able to survive in extreme environments, such as LCN10 and LCN70, belong to a small number of highly specialized species; nevertheless, the reservoir of diapausing eggs in the sediments was of the same order of size (10 3 -10 5 eggs per m −2 ) of those reported from less remote environments [16].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of diapausing eggs in different sections of the two sediment cores confirmed that their production is a fundamental survival strategy in high-altitude lakes. The accumulation in sediments of diapausing eggs of different species, generations and genotypes, represents a potential reserve of biodiversity [12,16], which buffers the consequent extinction risk from anthropogenic impacts and makes the population resilient to the settlement of invasive species [50,51]. Organisms able to survive in extreme environments, such as LCN10 and LCN70, belong to a small number of highly specialized species; nevertheless, the reservoir of diapausing eggs in the sediments was of the same order of size (10 3 -10 5 eggs per m −2 ) of those reported from less remote environments [16].…”
Section: Resultsmentioning
confidence: 99%
“…For some of these additional samples, both ND5 and COI sequences were available; for others, only ND5 sequence data exist (Table 1). Also among the existing sequences were Sierra Nevada samples published previously (Latta et al, 2010). Both gene regions, COI and ND5, were aligned to open reading frames.…”
Section: Resultsmentioning
confidence: 99%
“…All sequences were deposited in GenBank under accession numbers ‐ (ND5) and ‐ (COI). We also included in our analyses previously existing DNA sequence data from earlier publications (Colbourne et al ., ; Crease, ; Paland & Lynch, ; Mergeay et al ., ; Vergilino, Belzile & Dufresne, ; Latta et al ., ; Vergilino et al ., ). The final alignment of 1089 bp comprised 591 bp of COI and 498 bp of ND5 for 58 samples (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the egg banks and propagules could subsidise native populations with new individuals and buffer fish predation, but also, in this case, their roles have not been well studied (but see Parker et al 1996 andLatta et al 2010). There are also many overlooked aspects concerning the cascading effects of fish introduction (e.g.…”
Section: Ecological Consequencesmentioning
confidence: 99%